Obstetric Simulation Training to Breech Delivery, Shoulder Dystocia, Forceps, and Vacuum Experience - Jule Eric Horasanlı; NUR DEMİRBAS; Seyma Cıcek (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: This study aimed to create a simulation model in shoulder dystocia, breech delivery, and vacuum forceps applications, and to show the effect of education on the knowledge-skill level of the individuals involved.